Senior medical student attitudes towards patient communication and their development across the clinical elective year – A Q-methodology study - Schick, Kristina; Gartmeier, Martin; Berberat, Pascal O. (Frontline Learning Research, 2021)
To be proficient in communicating with patients, physicians need specified knowledge, skills and attitudes. Until now, medical educators have mostly focused on undergraduate students’ communication knowledge and skills in training and assessment. Attitudes towards communication with patients have been researched less frequently, but it is plausible that they also influence physicians’ behaviours in many ways. The present study investigates the communication-focused attitudes of senior medical students and their development through the clinical elective year using an innovative approach based on Q-methodology. We conducted a Q-methodology study using statements from the Kalamazoo Communication Skills Assessment Form. A total of 47 final-year medical students documented their attitudes towards communication by sorting these statements in regard to their importance into a normal distribution grid in medical interviews. Our innovative approach included three time points during the elective year at which these statements were sorted, with only a slight decrease of participants. We applied a Q-factor analysis and found three attitude profiles that were structurally stable over time. Attitude profile #1 focused on providing information and fostering shared decision making; profile #2 focused on the patients’ concerns and emotions while meeting the patients’ demands for sufficient information. Finally, the focus of attitude profile #3 was on using appropriate conversation techniques to structure communication and gather sufficient information. Overall, the respondents assigned increasing importance to building good relationships and making shared decisions with patients over time. Statements about structuring conversations and communication techniques were evaluated as less important by the end of the clinical elective year.